Léonard Bourdon : The Career of a Revolutionary, 1754-1807 - Sydenham, M. J. (Book collections on Project MUSE., 1999)
"Leonard Bourdon: The Career of a Revolutionary, 1754-1807 illustrates the ways in which one individual was affected by and influenced the long and turbulent course of the French Revolution. It also rescues an active, intelligent and interesting man from a prolonged period of scholarly neglect and redeems his reputation from being perceived as a particularly cruel revolutionary terrorist."--Jacket.